The Right to Be Forgotten in the Online Environment - Matic, Andreea Elena; Cornea, Valentina (Acta Universitatis Danubius. Juridica, 2022)
In the present paper we aim to analyze an important right: the right to be forgotten in the online environment, as a part of the right to respect for private and family life and also as a part of the protection of personal data, GDPR. In order to do that we will first refer to the content of the right to respect for the private and family life, then we will analyze the content of the specific regulation regarding the protection of the personal data of the natural person. More specifically, the right to be forgotten is established in the paragraph of the Regulation (EU) 2016/679 of the European Parliament and Council. We will explain the conditions which have to be fulfilled in order to use a natural person personal data and the situations in which this use is no longer allowed or necessary. In conclusions, we will argue that this specific right is very important in order to ensure the natural person that his or her personal data are only used in specific and necessary cases and then, after the specific situation has ended, the keeping and the use of those personal information is forbidden.